Trajectory Planning of Spherical Pendulum Pattern for Application in Creating Batik Patterns - Putri, Indah Radityo; Ekawati, Estiyanti; Budi, Eko Mursito; Juwandana, Alfisena; Mulyawan, Naufan Aurezan; Kho, Philip Inarta; Kudiya, Komarudin (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
Batik Pendulum is a new batik pattern created by Rumah Batik Komar using a single-string pendulum filled with wax. However, current production is still manual, so it is impossible to re-manufacture in large quantities. This research is part of a machine and software development project to produce Batik Pendulum, where this research will only focus on software development. The designed software will have a spherical pendulum trajectory planning feature through parameter changes. The spherical pendulum path was chosen because it has the same pattern as the currently produced Batik Pendulum. In planning the spherical pendulum trajectory, an algorithm that receives input in the form of parameters to produce a spherical pendulum pattern has been designed. From these inputs, it is proven that the proposed parameters can provide a variety of spherical pendulum patterns. Implementing the spherical pendulum trajectory planning in the software shows that the time required to change parameters until the output trajectory is generated is 1 – 2 seconds. So, there is no need for any feedback to the user.